1973
DOI: 10.1113/jphysiol.1973.sp010233
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic acinar cells: ionic dependence of the membrane potential and acetylcholine‐induced depolarization

Abstract: 1. Intracellular recordings of membrane potentials have been made in vitro from the exocrine acinar cells of the mouse pancreas using glass micro‐electrodes. 2. The mean membrane potential of the acinar cells during superfusion with Krebs‐Henseleit solution was −39·2 mV. Increasing [K]o tenfold decreased the membrane potential by 28 mV when [K]o was above 10 m M. This depolarization was not affected by atropine (1·4 × 10−6 M). Strophanthin‐G (10−3 M) slowly depolarized the cells at about 10 mV hr−1. 3. Brief e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
2

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 25 publications
8
49
2
Order By: Relevance
“…We attribute this to improvement in technique. The mean resting membrane potential measured in twenty experiments during superfusion with standard Tris buffered Ringer solution was -43-8 + 0-8 mV, which is similar to that found using KHB and more negative than the value reported by Matthews & Petersen (1973) of -35 mV.…”
Section: Resting Membrane Potentialsmentioning
confidence: 48%
See 2 more Smart Citations
“…We attribute this to improvement in technique. The mean resting membrane potential measured in twenty experiments during superfusion with standard Tris buffered Ringer solution was -43-8 + 0-8 mV, which is similar to that found using KHB and more negative than the value reported by Matthews & Petersen (1973) of -35 mV.…”
Section: Resting Membrane Potentialsmentioning
confidence: 48%
“…3) the studies were complicated PANCREATIC MEMBRANE POTENTIALS A23187-induced depolarization raised the question of whether the Ca2+ dependent depolarization might be due not to an increased divalent cation conductance but to an effect of the ionophore-mediated increased concentration of intracellular free Ca2+ on the permeability of the cell membrane to other ions. It has been concluded that the depolarization of the acinar cell membrane in response to ACh or pancreozymin is due to an increased permeability to Na+ (Matthews & Petersen, 1973;Nishiyama & Petersen, 1974. Consequently, the possibility that a secondary, Ca2+-dependent increase in the permeability to Na+ was involved in the depolarization by A23187 was tested.…”
Section: Ionic Dependence Of A23187-induced Depolarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been shown for acetylcholine (ACh) (Matthews & Petersen, 1973; Nishiyama & Petersen, 1974), cholecystokinin pancreozymin (CCK-PZ) and its relatives caerulein (Iwatsuki, Kato & Nishiyama, 1977) and gastrin-like peptides (Petersen & Ueda, 1975;Iwatsuki et al 1977). The electrical effects of bombesin on acinar cells have also been demonstrated more recently (Jwatsuki & Petersen, 1978).…”
Section: Introductionmentioning
confidence: 90%
“…Similar results were obtained in Cl-free isethionate solution where EAch was shifted to -1.4+0.7 mV (Fig.9). If we assume that the values for intracellular Na and K ion activities found (Nishiyama and Petersen 1974) (slope of 37 mV decade) than to the result in the mouse pancreas where the slope was found to be only 28 mV decade (Matthews and Petersen 1973).…”
Section: Resting Membrane Potential and Input Resistancementioning
confidence: 99%